Forbidden Marriages In Novel 'Kemarau' And Reality In The Life Of The Minangkabau Community - Desman, Febri; Barkah, Hendri Jihadul; Wahyuni, Wahida (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2024)
The novel “Kemarau” by A.A. Navis is a literary work that reflects the social life of the Minangkabau community. The main focus of this novel is on the life struggles of its characters. The issue of marriage, particularly the marriages involving the children in the novel, becomes the central focus of this research, aiming to uncover the problems and reasons behind the forbidden marriages portrayed in the story. Forbidden marriages in “Kemarau” arise from the father's attempt to overcome loneliness and the mother's mistake of not introducing or telling the story about the child's biological father. The causes of these forbidden marriages involve divorce, parental factors, and the influence of migration.In its analysis, this novel will be elaborated using sociological literature theory. This approach allows us to delve into the social life of a community reflected in a literary work and connect it with the reality of society during the birth and after the existence of the work. The research findings indicate that “Kemarau” is not only a literary masterpiece but also provides profound insights into the social dynamics of Minangkabau society. By delving into its social reality, the novel becomes a source of learning that enriches readers' experiences with the dynamics of life and marriage in Minangkabau culture